Harmonization of community health worker programs for HIV: a four-country qualitative study in Southern Africa - De Neve, Jan-Walter; Garrison-Desany, Henri; Andrews, Kathryn G.; Sharara, Nour; Boudreaux, Chantelle; Gill, Roopan; Geldsetzer, Pascal; Vaikath, Maria; Bärnighausen, Till; Bossert, Thomas John (PLoS medicine, 2017)
In a qualitative study, Jan-Walter De Neve and colleagues investigate how community health worker programs can be better integrated with the wider health systems in four countries in Southern Africa.
Gesehen am 12.09.2018